Anti-biofilm activity of anti-matrix molecules - А.Е. Abaturov (Zaslavsky O.Yu., 2020)
The extracellular matrix of biofilms ensures the fixation of the biofilm on the biological surface and the protection of its bacteria from external adverse factors. The main structural component of biofilms is an extracellular polysaccharide substance. Exopolysaccharides and amyloid-like fibers are considered key molecular structures that support the three-dimensional structure of biofilms. Until recently, it was assumed that most biofilm dispersion mechanisms are associated with the functioning of matrix degrading enzymes, such as glycoside hydrolases, polysaccharide lyases, and proteases. However, it has been demonstrated that small molecules play an independent role in the process of destruction of matrix exopolysaccharides and amyloid-like fibers. Among the compounds that violate the biofilm matrix, anti-matrix molecules, compounds interacting with microdomains of the bacterial membrane and bacterial surfactants (biosurfactants) are distinguished. It has been demonstrated that compounds of these groups can inhibit the formation of biofilms and contribute to the dispersion of biofilms. From the group of anti-matrix molecules, the polyamine compound norspermidine interacts with exopolysaccharides, and the derivatives of benzoquinone AA-861 and sesquiterpene lactone parthenolide interact with TasA-amyloid-like fibers. Norspermidine prevents the formation and dispersion of biofilms of various bacteria, including Acinetobacter baumannii, Bacillus subtili, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis. Compound AA-861 is active against biofilms, which are formed by the bacteria Streptococcus mutans, Bacillus cereus, Escherichia coli. Parthenolide disperses biofilms formed by Escherichia coli and Bacillus cereus. Zaragozic acid, interacting with microdomains of the bacterial membrane, disruptі the functioning of raft-associated bacterial proteins. Small anti-matrix molecules and bacterial membranes aimed at microdomains that initiate biofilm dispersion will certainly become the basis for the development of effective antibiofilm therapeutic drugs.